An analysis of grammatical and lexical cohesion in oral communication among Japanese language learners in university - Anthoney, Margaret; Mamat, Roslina (International Journal of Special Education, 2022)
This research was conducted to investigate the use of discourse cohesion aspects in Japanese Language oral communication in both grammatical cohesion and cohesion lexical. The purpose of the research is to know how the grammatical and lexical cohesion used in the conversation. The instruments were the Japanese Language students from Faculty of Major Language Studies (FPBU) in University Science Islam Malaysia (USIM). 10 students from 3rd years students were selected randomly to participate in the dialogue activity to collect the data. The data of this study which then were transcribed into written. The data collected were analysed qualitatively using cohesive devices based on Halliday and Hasan’s (1976). They are reference (personal, demonstrative and comparative), substitution (nominal, verbal and clausal), ellipsis (nominal, verbal and clausal), conjunction (additive, adversative, causal, temporal and others), and lexical cohesion (reiteration and collocation). The results of this research findings showed that the most frequently cohesions appeared in the dialogue are cohesion appeared in the dialogue are reference, substitution, and conjunctions. Meanwhile the occurrences of ellipsis, substitution and lexical reiteration were the least. The roles of the two cohesions can help students sentences to be cohesive in their oral communication in Japanese language. The study of cohesion of Japanese language oral communication can also offer some significance to pedagogical field.